The development of a wellness tourism program in Thailand: a community-based participatory action research approach with an empowerment theoretical framework - Thojampa, Somsak; Klankhajhon, Sirikanok; Kumpeera, Kittisak; Mongkholkham , Chuthathip; Ellen Mawn, Barbara (Universitas Airlangga, 2023)
Introduction: Thailand has not had a comprehensive effort to collaborate on a wellness tourism regional program for foreign travelers. The purpose of the study was exploring the key components necessary for a wellness tourism program in the lower northern region in Thailand. Methods: This is a qualitative, community-based, participatory action research guided by the empowerment theory. A descriptive qualitative approach to data collection and analysis was used to explore stakeholders' perspectives on the development of a wellness tourism program. A total of 40 key stakeholders from nine provinces in the lower north region of Thailand participated in two phases of the study's data collection. Individual and focus groups interviews were conducted and analyzed thematically. The purposive sample included semi-structured questionnaires among community leaders, village health volunteers, and workers from various occupations who lived in the communities. Results: Four themes emerged from the qualitative interviews and focus groups: 1) honoring local wisdom as the heart of a regional wellness tourism program; 2) the integration of historical traditions and regional lifestyles into a wellness tourism program; 3) the need for government supportive policies that help to fund community wellness initiatives to boost the local economy and tourism ;and 4) attention needed to improve the quality of life for the local communities while promoting wellness tourism in the region. Conclusion: This community-based participatory action research approach created a synergy among stakeholders from multiple provinces in the lower north region of Thailand.